Manners, Morals and Class in England, 1774-1858 - Morgan, M. author. aut Link
X, 196 p.
Keywords: This book analyses English social and occupational behavioural ideals from the courtesy book's demise in 1774 to the Medical Act's passage in 1858. Ideals from conduct and etiquette books mix gracefully with those displayed by professional groups, particularly medical practitioners, in an analysis that challenges conventional thinking about class and social change in early-industrial England. Dr Morgan's study will be essential reading for British historians, as well as for all those interested in how individuals establish personal identity and infuse confidence into human relations in an impersonal, urban society.